2020
DOI: 10.1371/journal.pone.0227808
|View full text |Cite
|
Sign up to set email alerts
|

Flying into the hurricane: A case study of UAV use in damage assessment during the 2017 hurricanes in Texas and Florida

Abstract: Unmanned aerial vehicles (UAVs) or drones have been used by disaster relief organizations in the United States since 2005. However, their place in the disaster response ecosystemthe standardization, utility, ethical, and legal challenges of drone use-remains largely unstudied. This case series describes how UAVs were used by two teams of responders for damage assessment purposes during the 2017 southeastern US Hurricanes Harvey and Irma. Data streams ranged from social media, direct observation, participant-ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…We only included publications in English, primarily because it is the only common language in which all researchers involved are proficient. We set the search to begin in 2000 since the first use of drones for disaster relief purposes was reported in 2005 during the response to Hurricane Katrina (Greenwood et al, 2020 ). Further, existing literature reviews on drones, as well as our own preliminary database search, indicated that almost no papers referring to drones were published before 2000 (Christen et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…We only included publications in English, primarily because it is the only common language in which all researchers involved are proficient. We set the search to begin in 2000 since the first use of drones for disaster relief purposes was reported in 2005 during the response to Hurricane Katrina (Greenwood et al, 2020 ). Further, existing literature reviews on drones, as well as our own preliminary database search, indicated that almost no papers referring to drones were published before 2000 (Christen et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…UAVs are thus ideal tools that have been used in a post-disaster scenario. For example, in March 2015, when Tropical Cyclone Pam, a category 5 storm, struck Vanuatu, UAVs were employed for mapping areas to assess the damage [37]. Similarly, when Typhoon Haiyan affected Philippines in November 2013, UAVs were used for aerial imaging to get real-time information on the disaster with the help of aerial imaging and the development of future frameworks for emergency response planning [38].…”
Section: -2020mentioning
confidence: 99%
“…A UAV, commonly known as the flying vehicle or drone, is a highly portable and miniature pilotless aircraft, which can fly in the sky and be controlled remotely [1], [2]. Recently, with the fast advancement in the electronics and communication technologies industry, UAVs have been extensively engaged in military, civil, and commercial sectors [3], [4]. The global UAV market is valued at USD 19.3 billion in 2019 and is expected to reach USD 45.8 billion by 2025, at a CAGR of 15.5percent from 2019 to 2025 [5].…”
Section: Introductionmentioning
confidence: 99%